KORELASI ANTARA MOTIVASI DAN KESIAPAN DENGAN HASIL BELAJAR PESERTA DIDIK KELAS IV SEKOLAH DASAR - Sri Suhelma; Siti Halidjah; Dyoty Auliya (Universitas Tanjungpura, 2021)
Abstract This research was aimed to find out the correlation between motivation and readiness with study result of grade IV students SDN 14 South Pontianak. This research was descriptive quantitative with correlation study. Samples in this study was 33 students of grade IV that selected using nonprobability sampling. The data source of this research was the questionnaire scales of motivation and readiness and a document of the learning scores of theme 1 sub theme 1. The result showed that students motivation was 77,18% categorized as good, the students readiness was 79,30% categorized as good, and learning results was 86,60 categorized as very good. The correlation between motivation with learning results was 0.552 categorized as medium. The correlation between readiness with learning results was 0,597 categorized as medium category. The correlation of motivation and readiness was 0,767 categorized as strong. The correlation of motivation and readiness with the learning results was 0,614 and its categorized as strong. Keywords : Learning Results, Motivation and Readiness.